Wind Catcher and Solar Chimney Integrated As An Alternative Ventilation For Urban Dense Settlements In Tropical Climate - Yoka Prima; Sugini Prima (International Journal of Architecture and Urbanism, 2019)
The high energy use for building operations in humid tropical climates is mostly used for operational mechanical ventilation such as air conditioning (AC) and fans. The use of large amounts of energy, especially fossil energy can reduce the quality of the environment, causing an increase in the temperature of the earth. Need more efforts for management of energy use by reducing fossil energy consumption. One effort that can be done is to replace mechanical production and utilize passive ventilation in buildings. this study is a literature review regarding the use of passive ventilation using a windcatcher integrated with solarc himneys. The use of windcatcher and the solar chimney is still very rare in Indonesia, but has the potential to solve thermal problems, especially in densely populated residential areas in cities that have the character of a humid tropical climate. The results of this study recommend criteria from windcatchers and soler chimney that might be applicable and adapt to the character of the urban humid tropical climate. Keyword: Wind Catcher, Solar chimney, Passive Ventilation, Urban Dense Settlements